Factors influencing the adoption of whole farm plans : a Wairarapa case study : a thesis presented in partial fulfilment of the requirements for the degree of Master in Applied Science in Agricultural Extension at Massey University - Cass, Sian (Massey University, 2008)
Hill country erosion is a serious environmental issue in New Zealand. After widespread damage from storms in 2004, Horizons Regional Council initiated the SLUI programme. This programme relies on whole farm plans (Whole Farm Business Plans) as the core tool to address erosion on hill country farms. Several regional councils in New Zealand, like Horizons, rely on whole farm plans and continue to seek ways to achieve a high level of voluntary adoption by farmers. A single case study was used to examine the phenomena of adoption of whole farm plans. This research answered the question: What factors influence the adoption by farmers of whole farm plans, and why these factors are influential? A review of historical farm plans identified plans most similar to Horizons Whole Farm Business Plans. These were located in the Wairarapa and this formed the case area. Farmers from two catchments in the Wairarapa, and key informants were interviewed to identify factors influencing adoption of farm plans. Findings from this study, in the main, support adoption diffusion literature for agricultural innovations. The specific mix of interrelated factors that influence the adoption of farm plans, and the reasons for their influence, were identified and described. Characteristics of this case included the widespread adoption of farm plans, and farmers' perceived farm plan implementation as secondary to the core farm business. Factors associated with the compatibility of the innovation to the core farm business and the credibility of the organisation delivering farm plans provided important influences on adoption of farm plans. The circumstances of the farmers and their farm did not strongly influence adoption in this study because farm plans are customised and take into account each individual's circumstances. For an innovation such as farm plans that is considered secondary to the core farm business, factors easing implementation were important. This was contributed to by the characteristics of the innovation and by the delivery and support from the organisation. Key people played a significant role in farmers' decisions to adopt a farm plan.
Keywords: New Zealand; Agricultural innovations; Farm management; Decision making; Farmers -- Attitudes